The effect of eave and window modifications on house entry behavior of Anopheles gambiae - Jeroen Spitzen; Martin J. Lankheet; Remco P. M. Pieters; Miracle Gadamika; Ike Phiri; Antoine Cribellier; James G. Logan; Constantianus J. M. Koenraadt; Kamija S. Phiri; Florian T. Muijres; Robert S. McCann (Parasites & Vectors)
Abstract Background Anopheles gambiae mosquitoes transmit malaria parasites to humans mostly by biting them indoors at night, entering houses predominantly through ventilation openings such as open eaves and windows. In the study reported here, we studied how flying An. gambiae approach and enter a house, and whether barriers to reduce mosquito house entry alter mosquito flight patterns. Methods Stereoscopic high-speed videography was used to reconstruct nearly 70,000 three-dimensional tracks of mosquitoes flying around a house during 30 experimental nights, with five combinations of closed or screened eaves and windows (eaves open – windows open; eaves open – windows closed; eaves open – windows screened; eaves closed – windows screened; eaves screened – windows screened). Results In this study the eave and window treatments did not affect the number of mosquitoes attracted to the house. In all cases, mosquitoes were most active during the early evening, with lower but sustained activity throughout the night. Most An. gambiae mosquitoes approached the house by flying directly towards the eave in an upward sloping path with minimal left–right deviations, and most flight activity near the house was directly in front of the eave. Due to the highly attractive nature of the eave area of the house, window treatments had limited to no effect on the number of house entries when eaves were left open, highlighting the importance of closing or screening eaves to prevent mosquito house entry. For the screened eave treatment, An. gambiae spent about 10-fold more time near the eave over the course of the night compared to the time spent near the eave in the open or closed eave treatments. Moreover, these mosquitoes returned multiple times, persistently trying to enter the house. When the eaves were fully closed, mosquitoes ultimately diverted from the eave area towards the screened window, but the initial approach flights remained towards the closed eave. Conclusions Taken together, these results demonstrate the tendency of An. gambiae to direct house entry toward the eaves, and to only divert to other house entry points as a secondary option. The persistent mosquito flight near screened eaves may provide guidance for the placement of outdoor vector control tools. Graphical abstract